The qualitative characteristics of the soil of the Iraqi coast - Fayyad, Nasreen; Mankhi, Sadeea (Al-Adab Journal, 2023)
The current study dealt with the qualitative characteristics of the soil of the Iraqi coast and the future potential for investment. The outputs of this study could constitute an applied database for future projects, if there was serious development and management of the coastal environment and investment of the waterfront and its development in an optimal way to keep pace with coastal investments in other regions of the world that have conditions similar to the conditions of the characteristics The quality of the soils of the Iraqi coast. The study area, which is represented by the Iraqi coast, is located in the province of Basra in southern Iraq, with an area of ​​1248,408 km2, represented by the end of the land and its connection with the waters of the Arabian Gulf, and astronomically, it lies between (30ً 38َ 48ْ) – ( 50ً 50َ 47ْ) east and two latitudes ( 18ً 12َ 30ْ) (39ً 54َ 29ْ) North. An introduction to soil and classification of soils in the study area was reviewed according to Biornck classification and FAO classification. (10) samples were taken from the study area along the Iraqi coastline. The physical properties of soils, including soil texture, were represented In the soil texture triangle, the research also dealt with the chemical properties of soil and the most important elements affecting the study area, including organic matter (OM) and pH. Ni (ph), salinity (Sat), rate of dissolved salts (TDS), positive ions including calcium ion (Ca+), sodium ion (Na+), iron (Fe+), magnesium (Mg+), negative ions including sulfate (SO4-), bicarbonate (HCO3-) and chlorides (CL-) and nitrates (NO3-), and the conclusions were reached to several things, including that the soil of the Iraqi coast is of the alluvial clay type, which is suitable for cultivation in most of the coastal regions.